QUALITY ANALYSIS OF GOODS DELIVERY SERVICE USING SIX SIGMA APPROACH IN PT. KAMADJAJA LOGISTICS SURABAYA - Indah Apriliana Sari; Achmad Ubaidillah (UNIPA PRESS, 2020)
Complaints within the companyare often found in service companiesbecause of the complexity of theactivities in the service company. Speedand accuracy are important for freightforwarding companies. The purpose ofquality control is to reduce complaints(defects) and even achieve zero defects.The focus of this research is to analyzethe service attributes that need to bedeveloped by PT Kamadjaja Surabayawith the Six Sigma method. The resultsof this study indicate that the quality ofservice has not been maximized which isstill far from the level of 6 sigma withDPMO 3.4 for that service needs to beimproved. This is indicated from theresults of measurements with the sixsigma method showing an averageperformance score of 3.74; expectationscore of 4.90; gap -1,16; satisfactionlevel is 76.37%, DPMO value is 251733,and sigma level is 2.25. It becomes thedominant attribute that causes customerdissatisfaction